Exploring the value Australian community leaders see in a system dynamics model calibrated with local data: social norms and childhood obesity - Karien Stronks; Loes Crielaard; Steven Allender; Mary Nicolaou; Andrew D Brown; Joshua Hayward (BMJ Open)
Objectives Systems approaches (SAs) seek to understand the dynamics behind system behaviour and formulate effective actions given these dynamics. In public health, SAs often rely on qualitative systems maps visualising factors and their interconnections, frequently developed through group model building. Quantitative system dynamics models (SDMs) can offer additional insights: SDMs can simulate how system behaviour would change if we were to make an adjustment to the system, in what-if scenarios. We explored what (added) value Australian community leaders involved in SAs see in an SDM for understanding a system and its behaviour.Setting The Whole of Systems Trial of Prevention Strategies for Childhood Obesity (WHOSTOPS), a community-level collaboration between researchers and community leaders in South-Western Victoria, Australia.Design We calibrated an existing small and high-level SDM with local data from the WHOSTOPS communities, so that the simulations pertained to their local context. The SDM was developed to simulate potential interventions addressing either social norms regarding body weight or individual weight-related behaviour. We presented the SDM to the community leaders via an interactive interface in an online workshop.Participants We calibrated the SDM using WHOSTOPS’ baseline measurement (2015), with an 80% participation rate among eligible children (1792/2516). 11 community leaders participated in the workshop.Results The community leaders’ first impression of the SDM was that it could be a valuable additional tool, particularly because of its ability to compare what-if scenarios resembling individual vs systems perspectives, intuitive presentation of simulation results, and use of local data.Conclusions Our preliminary exploration showed that the small and high-level SDM, using what-if scenarios reflecting interventions on different system levels, could contribute to the understanding and communication of (community-based) SAs.